Kinase Suppressor of Ras 2 (KSR2) expression in the brain regulates energy balance and glucose homeostasis - Lili Guo; Diane L. Costanzo-Garvey; Deandra R. Smith; Beth K. Neilsen; Richard G. MacDonald; Robert E. Lewis (Elsevier, 2017)
Objective: Kinase Suppressor of Ras 2 (KSR2) is a molecular scaffold coordinating Raf/MEK/ERK signaling that is expressed at high levels in the brain. KSR2 disruption in humans and mice causes obesity and insulin resistance. Understanding the anatomical location and mechanism of KSR2 function should lead to a better understanding of physiological regulation over energy balance. Methods: Mice bearing floxed alleles of KSR2 (KSR2fl/fl) were crossed with mice expressing the Cre recombinase expressed by the Nestin promoter (Nes-Cre) to produce Nes-CreKSR2fl/fl mice. Growth, body composition, food consumption, cold tolerance, insulin and free fatty acid levels, glucose, and AICAR tolerance were measured in gender and age matched KSR2−/− mice Results: Nes-CreKSR2fl/fl mice lack detectable levels of KSR2 in the brain. The growth and onset of obesity of Nes-CreKSR2fl/fl mice parallel those observed in KSR2−/− mice. As in KSR2−/− mice, Nes-CreKSR2fl/fl are glucose intolerant with elevated fasting and cold intolerance. Male Nes-CreKSR2fl/fl mice are hyperphagic, but female Nes-CreKSR2fl/fl mice are not. Unlike KSR2−/− mice, Nes-CreKSR2fl/fl mice respond normally to leptin and AICAR, which may explain why the degree of obesity of adult Nes-CreKSR2fl/fl mice is not as severe as that observed in KSR2−/− animals. Conclusions: These observations suggest that, in the brain, KSR2 regulates energy balance via control of feeding behavior and adaptive thermogenesis, while a second KSR2-dependent mechanism, functioning through one or more other tissues, modulates sensitivity to leptin and activators of the energy sensor AMPK. Keywords: Obesity, Glucose metabolism, Insulin resistance, KSR2, AMPK